The degradation of poly(1-butene) extrudates subjected to artificial and natural aging - Zenzingerova, Sona; Kudlacek, Michal; Benicek, Lubomir; Jaska, David; Navratilova, Jana; Gajzlerova, Lenka; Cermak, Roman (Iranian polymer journal, 2024)
In this work, we examined the degradation behavior of isotactic poly(1-butene) (PB-1) under artificial aging and natural weathering conditions. PB-1 samples underwent accelerated aging through UV irradiation and natural weathering. Chemical and structural changes in the degraded samples were characterized using Fourier-transform infrared–attenuated total reflectance (FTIR–ATR) spectroscopy, surface analysis, and wide-angle X-ray scattering (WAXS). The mechanical properties were evaluated via tensile testing. FTIR–ATR analysis revealed the presence of carbonyl groups in the degraded samples, indicating oxidative degradation. Surface observations employing scanning electron microscopy (SEM) revealed the formation of surface cracks in both samples, with differing crack initiation mechanisms. The two aging methods affected the mechanical properties of the samples: artificial aging induced a gradual reduction in both tensile modulus and strength, whereas natural weathering engendered a marginal increment in modulus alongside diminished strength. Additionally, elongation-at-break value witnessed a marked decrease in both sample sets during the preliminary stages of degradation. This work employed accelerated time equivalent, obtained by juxtaposition of the values of carbonyl index during both artificial aging and natural weathering and their interpolation to determine the degradation rate and adequately to correlate the final properties of the aged PB-1. It was observed that surface morphology and mechanical attributes of degraded samples were subject to additional influences such as temperature, humidity, and precipitation during natural weathering. This research work provided significant insights into PB-1 degradation mechanisms and effect of different aging conditions on its performance. Graphical abstract